NFCPlay: using NFC tags on VR mobile games to overcome the lack of input on VR Headsets - dos Santos, Ezequiel França; Ramos, Reinaldo Augusto de Oliveira; Junior, José Carlos Buesso (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
User input in Virtual Reality (VR) mobile games on the touch screen have been a problem in the gaming industry for many years. Some solutions using timers, waiting to look at something to act, have been proposed and used in several games. Some VR Headsets models had a magnetic button on the side. However, this button caused interference in the magnetometer and the GPS module, essential modules for developing games using VR. This work aims to present the use of an NFC tag (Near Field Communication) as an input mechanism for the player to overcome the lack of input on VR Headsets.